Synergistic prognostic value of base excess and fibrinogen in predicting mortality after severe trauma - Jonghee Han; Junepill Seok; Su Young Yoon; Se Heon Kim; Jin Young Lee; Jin Bong Ye; Jin Suk Lee; Younghoon Sul (Hong Kong Journal of Emergency Medicine)
Abstract Purpose Although base excess (BE) and fibrinogen are established prognostic markers in severe trauma, their combined predictive power remains uncharacterized. This study aimed to determine whether admission BE and fibrinogen levels independently and interactively predict 30‐day mortality in severely injured adult trauma patients (ISS ≥ 15), thus informing improved resuscitation strategies. Methods This retrospective cohort study analyzed 513 adult trauma patients (ISS ≥ 15) admitted to a level I trauma center. Optimal BE and fibrinogen cutoffs were identified via ROC analysis. Adjusted Cox proportional hazards regression, controlling for key confounders, assessed the association between these biomarkers and 30‐day mortality. Results 30‐day mortality was 12.1% (n = 62). Low BE and low fibrinogen were independently associated with increased mortality (p < 0.001 and p = 0.009, respectively). Critically, a strong synergistic interaction was identified (p < 0.001), with patients exhibiting both low BE and low fibrinogen showing a markedly increased mortality risk (HR 8.46, 95% CI 3.60–19.90, and p < 0.001). Conclusion Low admission BE and fibrinogen levels are strongly associated with increased mortality in severe trauma exhibiting a significant synergistic effect. These findings necessitate a multimodal approach to resuscitation targeting both metabolic acidosis and coagulopathy.